The draft genome of whitefly Bemisia tabaci MEAM1, a global crop pest, provides novel insights into virus transmission, host adaptation, and insecticide resistance. Issue 1 (December 2016) - Chen, Wenbo; Hasegawa, Daniel; Kaur, Navneet; Kliot, Adi; Pinheiro, Patricia; Luan, Junbo; Stensmyr, Marcus; Zheng, Yi; Liu, Wenli; Sun, Honghe; Xu, Yimin; Luo, Yuan; et al.
Abstract Background The whiteflyBemisia tabaci (Hemiptera: Aleyrodidae) is among the 100 worst invasive species in the world. As one of the most important crop pests and virus vectors, B. tabaci causes substantial crop losses and poses a serious threat to global food security. Results We report the 615-Mb high-quality genome sequence ofB. tabaci Middle East-Asia Minor 1 (MEAM1), the first genome sequence in the Aleyrodidae family, which contains 15, 664 protein-coding genes. TheB. tabaci genome is highly divergent from other sequenced hemipteran genomes, sharing no detectable synteny. A number of known detoxification gene families, including cytochrome P450s and UDP-glucuronosyltransferases, are significantly expanded inB. tabaci . Other expanded gene families, including cathepsins, large clusters of tandemly duplicatedB. tabaci -specific genes, and phosphatidylethanolamine-binding proteins (PEBPs), were found to be associated with virus acquisition and transmission and/or insecticide resistance, likely contributing to the global invasiveness and efficient virus transmission capacity ofB. tabaci . The presence of 142 horizontally transferred genes from bacteria or fungi in theB. tabaci genome, including genes encoding hopanoid/sterol synthesis and xenobiotic detoxification enzymes that are not present in other insects, offers novel insights into the unique biological adaptations of this insect such as polyphagy and insecticide resistance. Interestingly, two adjacent bacterial pantothenate biosynthesis genes, panB andpanC, have been co-transferred intoB. tabaci and fused into a single gene that has acquired introns during its evolution. Conclusions TheB. tabaci genome contains numerous genetic novelties, including expansions in gene families associated with insecticide resistance, detoxification and virus transmission, as well as numerous horizontally transferred genes from bacteria and fungi. We believe these novelties likely have shapedB. tabaci as a highly invasive polyphagous crop pest and efficient vector of plant viruses. The genome serves as a reference for resolving theB. tabaci cryptic species complex, understanding fundamental biological novelties, and providing valuable genetic information to assist the development of novel strategies for controlling whiteflies and the viruses they transmit.